Recursos Humanos em Saúde: Avaliação dos Impactos do PROFAE nas Condições de Vida dos Trabalhadores Atendidos pelo Projeto em Boa Vista-RR - Noronha Filho, Ananias (2009)
The object in study of this dissertation is the identification impacts of the Project of Nursing Professionalization Workers (PROFAE) in the workers' life conditions assisted by the Project from the period from 2000 to 2004, in Boa Vista city, capital of Roraima State. It was used the historical approach and the dialectic method, contexting the object in the widest process of the social relationships, in national and international extent, and establishing their mediations with the specific historical conditions in which happened its constitution. The research explicit the links with economical politics and cultural questions in which the nursing profession is inserted in the contemporary capitalism. Through the articulation between the spheres of the singular and the universal, it evidences its subordination to the reorganization of the capital under new production parameters and accumulation, results of the answer of the world capitalism in the general crisis that turned more evident in the 70 . The theoretical research had as main primary sources national official documents, bibliographical rising that looked to identify the relationship of the Project with the capital reproduction, mainly in what concerns the social work division in the nursing area and the measuring of the professional education in health and the fetish that the profession presents mainly for the workers of medium level education. The work questions the conception of PROFAE as repairment of a social debt to the nursing workers. The study evidences the marginal position attributed to the professional education in the Brazilian educational system. The impacts are identified in which project provided to the workers assisted in Boa Vista, RR, such impacts could only be demarcated starting from the questionnaire application elaborated by the definition of variables and indicators related to the workers' life and the work conditions possed. The individual improvements reached by the workers that participated in the research, also echoed in improvements in the quality of the health attendance by the health units of in Boa Vista. Such affirmative feels due to the analysis of the research data once, according to the workers that participated in the research, they feel much reassured, after accomplishing the course, to execute nursing techniques, besides identifying what can accomplish or not in the nursing attendance given to the users that look for the services where they are working. Finally stands out that PROFAE, while engendered politics under the aegis of the neoliberal prescription, does not guarantee the existence of a public politics a more solid and permanent formation for the health workers .